2004
DOI: 10.1289/ehp.6265
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for assessing reproductive development and health: Part 1--Pubertal development.

Abstract: The proposed National Children's Study has helped raise awareness of the issues related to children's health and the importance of monitoring the growth and development of children from preconception through adulthood. Many genetic predispositions can adversely impact the normal development process, and various environmental exposures have been linked to adverse reproductive health in rodent models and a small number of accidental human exposures. To monitor reproductive health and identify adverse effects at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 91 publications
1
47
0
4
Order By: Relevance
“…Available approaches for the assessment of pubertal onset and progression have recently been reviewed, 1 including the use of Tanner stages 2,3 for female breast and pubic hair development and male gonadal and pubic hair development. Menarche is also an important marker used for assessing puberty in girls.…”
Section: Regulation Of Normal Puberty Onset and Progression In Humansmentioning
confidence: 99%
“…Available approaches for the assessment of pubertal onset and progression have recently been reviewed, 1 including the use of Tanner stages 2,3 for female breast and pubic hair development and male gonadal and pubic hair development. Menarche is also an important marker used for assessing puberty in girls.…”
Section: Regulation Of Normal Puberty Onset and Progression In Humansmentioning
confidence: 99%
“…Puberty-timing measures used in studies have expanded in the past century to include measures that capture onset and progression of puberty (eg, Tanner stages) as well as completion. [5][6][7][8][9] Although researchers disagree about whether children are entering and/or progressing through puberty earlier today than in the mid-1900s, some recent analyses of US cross-sectional data concluded that girls are reaching puberty earlier over this time span, as measured by age at breast development stage, pubic hair development stage, and/or age of menarche. [10][11][12][13][14] Conversely, other studies concluded that there is no compelling evidence of an earlier age of menarche when comparing data collected in the 1950s and 1960s with data collected between 1988 and 1994.…”
mentioning
confidence: 99%
“…One of the complexities in comparing different studies is that pubertal milestones are not as easily identified in boys and therefore methodology varied from reliance upon visual inspection of staging to the use of surrogate measures such as voice change or attainment of adult height as endpoints associated with sexual maturation (Rockett et al 2004). Most studies lacked measurement of testicular volume, which is the most reliable method of assessing pubertal onset and progression.…”
Section: Figurementioning
confidence: 99%
“…Early signs of pubertal onset and progression may only be detectable on a detailed physical examination, which is rarely performed in epidemiological studies (Rockett et al 2004). Studies have attempted to use clinical surrogates such as peak growth velocity, but this occurs late in puberty and therefore may correlate with the tempo rather than the onset of puberty.…”
Section: Edcs and Human Pubertymentioning
confidence: 99%